IMPROVING THE SECOND YEAR STUDENTS' SPEAKING ABILITY THROUGH PROJECT-BASED LEARNING (PBL) AT MTSN MODEL MAKASSAR - Muhammad Saddam Abubakar (Universitas Islam Negeri Alauddin Makassar, 2015)
This research was conducted to the second year students of MTsN Model Makassar in academic year 2014-2015. The subjects of this research consisted of thirty seven students. The objective of this research was to improve the students’ speaking ability through Project Based Learning (PBL) method. This research applied Project Based Learning (PBL) to improve students’ speaking ability. It is aimed to know the process teaching learning of using Project Based Learning (PBL) to improve students’ speaking ability. The researcher used Classroom Action Research (CAR) as the research method. The researcher conducted two cycles; each cycle consisted of three meetings. The data were collected use three instruments. First instrument was observation sheet. The aims of this observation were to know the students’ activity during the teaching and learning process, and to know the activeness of learning in improving the students’ speaking ability, the second instrument was speaking test to measure the student’s speaking skill improvement, and the last instrument was questionnaire to know the students’ attitude toward project based learning (PBL).Keywords: speaking aspects, speaking activity, project-based learning